Thrombotic thrombocytopenic purpura: A rare complication of acute pancreatitis. Issue 5 (28th February 2019) - Shah, Jimil; Mandavdhare, Harshal S; Birda, Chhagan Lal; Dutta, Usha; Sharma, Vishal
Abstract : Thrombotic Thrombocytopenic Purpura (TTP) is a poorly understood entity involving multiple organs and having grave prognosis if not treated promptly. Acute pancreatitis (AP) is a rare cause of TTP and TTP is also a rare complication of acute pancreatitis. TTP is induced in AP by poorly understood mechanism, which involves multiple pathways apart from only ADAMTS13 deficiency. Here, we report a case of a 32‐year‐old male who developed acute pancreatitis due to chronic alcoholism. He developed signs of TTP from Day 4 of his onset of pain. High clinical suspicion and prompt initiation of plasmapheresis was associated with good outcome. In this case report, we have discussed details of our case and the different mechanisms involved in pathogenesis of TTP in AP and their outcome with prompt management. Abstract : We report a case of a 32‐year‐old male who developed acute pancreatitis due to chronic alcoholism. He developed signs of thrombotic thrombocytopenic purpura (TTP) from Day 4 of onset of pain. High clinical suspicion and prompt initiation of plasmapheresis were associated with good outcome.